Chitinase-Mediated Suppression of Groundnut Stem Rot Pathogen (Sclerotium rolfsii Sacc.) by Bacillus amyloliquefaciens RRR16 (International Journal of Scientific Research in Science and Technology, 2026)
Groundnut (Arachis hypogaea L.) is one of the most important oilseed crops, but its production is severely affected by stem rot disease caused by Sclerotium rolfsii. The present study investigates the potential of a chitinase-producing Bacillus amyloliquefaciens strain GR16 for biological control of S. rolfsii. The isolate was obtained from rhizospheric soil of healthy groundnut plants and identified through morphological, biochemical, and molecular characterization. B. amyloliquefaciens RRR16 exhibited strong chitinolytic activity on colloidal chitin agar plate and significantly inhibited the mycelial growth of S. rolfsii in a dual culture assay with 92.86 % inhibition. The results indicate that B. amyloliquefaciens RRR16, through its chitinolytic mechanism, can serve as an efficient biocontrol agent for sustainable management of groundnut stem rot disease.